1996
DOI: 10.1074/jbc.271.27.15981
|View full text |Cite
|
Sign up to set email alerts
|

A -Acting DNA Element Located between TATA Box and Transcription Initiation Site Is Critical in Response to Regulatory Sequences in Human Angiotensinogen Gene

Abstract: The promoter of the human angiotensinogen (hAG) gene functioned in its own core promoter context but not when replaced with simian virus 40 (SV40) core promoter, suggesting the presence of a transcriptionally important cis-acting sequence. Electrophoretic mobility shift assays demonstrated that a ubiquitously expressed nuclear factor, AGCF1, bound to AGCE1 (hAG core promoter element 1; positions ؊25 to ؊1) located between the TATA box and transcription initiation site. Substitution mutation in AGCE1 which disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0
3

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 40 publications
1
65
0
3
Order By: Relevance
“…[34][35][36] Studies conducted on chimpanzees showed that when exposed to high salt diets their BP levels increase, which is consistent with adaptation to a low sodium environment. 37 This evidence supports the hypothesis that modern humans inherited from their ancestors a gene that was adaptive in an environment low in sodium.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…[34][35][36] Studies conducted on chimpanzees showed that when exposed to high salt diets their BP levels increase, which is consistent with adaptation to a low sodium environment. 37 This evidence supports the hypothesis that modern humans inherited from their ancestors a gene that was adaptive in an environment low in sodium.…”
Section: Discussionmentioning
confidence: 62%
“…27 However, when tests of selection are applied to the entire gene, no evidence of a selective sweep or any other form of selection is present. Furthermore, other sites, like the À217, À20 and À18 have been shown to affect basal transcription rates 34,36 and therefore the À6 position is just one among many that could influence the levels of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The role and form of the TATA box are also more complicated than originally conceived. While in some yeast and human genes the canonical TATAAA motif can functionally survive mutation to other AT-rich arrays [14,19,31,32], in other genes, such mutations either abolish transcriptional function or move the start site [33,34]. There is also the situation in which a TATA box is present as the wild-type motif and can bind TBP or TFIID, but yet is dispensable for significant rates of transcription [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Although the binding of additional transcription factors to core promoters at sites other than the TATA box or initiator has been shown in other genes (e.g. AGCE1 binding at bp k26 to k9 of the angiotensinogen gene ; [14]), the results obtained here are distinguished from similar experiments with other TATA\initiator-containing core promoters, in which a third (or more) factor(s) was\were not sufficiently associated to the basal apparatus to dislodge it from a wild-type core (e.g. [52]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation